Jugun Ianfu: The Hermeneutics of Comfort Women in Dulaang UP’s “Nana Rosa” - Jarabo, Junine Ray (Future Science / FSH-PH Publications, 2025)
This research analyzed the portrayal of comfort women in Dulaang UP’s stage play Nana Rosa through its text and performance by applying the inte-grated Gadamer’s 6 steps of Hermeneutics and Hall’s Representation Theory. The study found that the communicated meanings could be interpreted through its elements, such as the characters, storytelling, the visual design, and auditory elements by understanding the underlying context of the stage play, The results indicated that the effectiveness of the play’s representation of comfort women is based on how it was staged. The study highlights the need by interpreting the play through observation by exploring its intention and issues that need to be addressed, assessing its coherence and how it shapes the constructed meaning presented with subtexts and symbols. How-ever, an in-depth analysis of the entire play by selecting scenes and dialogues showed multiple notions based on its presentation. A detailed hermeneutic framework is used to determine the play’s effective representation of com-fort women.